Effects of Gradual Reintroduction of Visual Architectural Distractors on Sensory Profiles and Visual Attention in Children with Autism: an In-novation in Sensory Integration Therapy, a pilot study - mehrshahi, shayan; Mirzakhani Araghi, Navid (Journal of Clinical Physiotherapy Research, 2025)
Background: Objective measures such as eye tracking offer promise to quantify attention modulation. We report a controlled intervention in which visual distractors in the therapy room were removed and then systematically reintroduced, examining changes in sensory profiles and eye-tracking metrics. Methods: Five children with ADHD were enrolled in intervention group and 5 as controls. At baseline, all participants completed the Short Sensory Profile-2 (SSP-2) and an eye-tracking session to detect primary visual distractors. During a first 3-month, all distractors were removed in both groups, and standard therapy proceeded. After 3 months, all assessments were repeated. In the intervention group, over the next 3 months, architectural distractors were gradually reintroduced (one every 3 weeks) while the control group remained in the distraction-free environment. At the end of 6 months, SSP2and eye tracking were reassessed and compared. Results: In the intervention group, mean total SSP2score improved) from 130 ± 8 at baseline to 145 ± 10 after the first 3 months (p = 0.02), then declined modestly to 138 ± 9 after the second 3 months (p = 0.04). Eye-tracking metrics showed significant reductions in distractor engagement in the second period relative to the midpoint (p<0.03). The control group showed continued gradual improvement in SSP2 (128 ± 7 → 135 ± 9 → 140 ± 10) but no major change in distractor zone metrics. The net SSP2change in intervention group attenuated compared to control (p = 0.04). Conclusions: Findings support the use of eye tracking as an objective outcome measure in sensory-based interventions and highlight the importance of environmental control in autism therapy. Larger controlled trials are needed.